Kaempferol conjugated gold nanoclusters enabled efficient for anticancer therapeutics to A549 lung cancer cells - Govindaraju S (Dove Medical Press, 2019)
Saravanan Govindaraju,1,* Arivazhagan Roshini,2,* Min-Ho Lee,3 Kyusik Yun11Department of Bionanotechnology, Gachon University, Gyeonggi-do 13120, Republic of Korea; 2Department of Neuroscience and Physiology, SUNY Upstate Medical University, Syracuse, NY 13210, USA; 3School of Integrative Engineering, Chung-Ang University, Seoul 06974, Republic of Korea*These authors contributed equally to this workBackground: Kaempferol (K) is a recognized anticancer drug that can conjugate with small-size gold nanoclusters (AuNCs).Materials and methods: K-AuNCs were synthesized and their use as an anticancer drug was explored using A549 lung cancer cells. Colony formation and cell migration assays were carried out. The morphology of the K-AuNCs treated A549 cells was explored using bio-atomic force microscopy.Results: The K-AuNCs were 1-3 nm in diameter and emitted strong fluorescent at 650 nm following excitation at 550 nm. The stretching and bending nature of the K-AuNCs were analyzed by the Fourier transform infrared spectroscopy. The presence of kaempferol in the AuNCs were confirmed by the PL spectroscopy.Conclusion: The synthesized K-AuNCs mainly targeted and damaged the nuclei of the cancer cells. This composite nanocluster was less toxicity to the normal human cell and higher toxicity to the A549 lunch cancer cell and these material is potential for anticancer drug delivery and bio imaging applications.Keywords: gold cluster, fluorescent property, biocompatible, flavonoids, anticancer activity